Far from the madding crowd - Hardy, Thomas, 1840-1928.; Falck-Yi, Suzanne B. (New York : Oxford University Press, 2002)
Bathsheba Everdene is courted by three young men: an adventurer, a young farmer who becomes bailiff of the farm she inherits, and a neighboring farmer.
Includes bibliographical references (p. [xxxviii]-xlii).
Adult
Keywords: Women farmers -- Fiction; Didactic fiction; Pastoral fiction; Women farmers -- Fiction; Wessex (England) -- Fiction; Wessex (England) -- Fiction